2020
DOI: 10.1155/2020/6720607
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with U5M in the Afar Region of Ethiopia

Abstract: Background. Ethiopia has experienced a significant reduction of under-five mortality over the past few decades. But still, the country is far from the Sustainable Development Goals (SDGs) of 2030. This study aims to identify the potential associated factors of under-five mortality in the Afar region, Ethiopia. Methods. Data from a national representative cross-sectional survey of Ethiopian Demographic and Health Survey of the year 2016 were used. Data were collected from the population of all under-five childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
3
7
1
1
Order By: Relevance
“…The possible response might be due to poor nutrition and difficulty accessing health services. Neonates born from high-income households would be able to meet needs and services such as health facilities, quality of life, quality of water, and increased provision of sanitation [32]. These results were consistent with previous reports [18,31], which suggest that a lower wealth quintile was associated with child mortality.…”
Section: Discussionsupporting
confidence: 92%
“…The possible response might be due to poor nutrition and difficulty accessing health services. Neonates born from high-income households would be able to meet needs and services such as health facilities, quality of life, quality of water, and increased provision of sanitation [32]. These results were consistent with previous reports [18,31], which suggest that a lower wealth quintile was associated with child mortality.…”
Section: Discussionsupporting
confidence: 92%
“…The strengths of this study included the large sample size and the accessibility of data with information from a nationally representative sample of the 2016 EDHS, which had several confounders of infant mortality in Ethiopia (e.g., EDHS, 2017). Our study thus contrasts with past studies in Ethiopia that have worked with a small and nonrepresentative sample (e.g., Gebremichael & Fenta, 2020; Tesema et al, 2021).…”
Section: Discussioncontrasting
confidence: 90%
“…Moreover, in Ethiopia, Gebremichael and Fenta (2020) and Tesema et al (2021) have comprehensively investigated the association between mothers' education and infant mortality; however, these studies need to be revised to consider proximate factors and confounding variables. Furthermore, Bereka et al, (2017) only focused on the Ethiopian Somali Regional State, while Gebretsadik and Gabreyohannes (2016) only included high‐mortality regions in Ethiopia by using a small sample.…”
Section: Introductionmentioning
confidence: 99%
“…29 However, the findings of this study are not in line with the study conducted in the Afar region, which has shown family sizes have a significant reduction in child mortality. 35 …”
Section: Discussionmentioning
confidence: 99%
“…29 However, the findings of this study are not in line with the study conducted in the Afar region, which has shown family sizes have a significant reduction in child mortality. 35 The risk of under-five deaths was higher among children who lived in houses built with inadequate materials than in those with standard and moderate housing materials (a house built in the absence of windows and inadequate materials from which the roof was built). The house built with moderate housing materials (windows installed) reduced the risk of dying more than a child in a house built with inadequate materials.…”
Section: Discussionmentioning
confidence: 99%